Cancer cell behaviour following parasite exposure - Jacobs, Brittany-Amber (Division of Immunology, 2019)
Infectious diseases, including helminthiases, are estimated to cause 16.1% of global cancer cases. While certain helminths are conclusive causes of cancer, others have been shown to reduce the disease. It is currently unknown why differing helminth infections promote or prevent cancer development and progression, or which cellular mechanisms are altered following exposure. Using several in vitro and in vivo techniques, this study aimed to determine the effect that certain helminths have on the progression of cervical and colorectal cancer. The results revealed that antigen from the hookworm Nippostrongylus brasiliensis significantly reduced cervical cancer cell migration and the expression of two markers of metastasis: vimentin and N-cadherin. Importantly, N. brasiliensis antigen significantly lowered the expression of cell-surface vimentin, while decreasing Human Papillomavirus type16 pseudovirion internalization. In vivo infection with N. brasiliensis significantly decreased vimentin expression within the female genital tract, confirming the relevance of these in vitro findings. Furthermore, exposure to antigen from the gastrointestinal nematode Heligmosomoides polygyrus decreased the in vitro proliferation of human and mouse colorectal cancer cells and simultaneously increased the expression of cell cycle regulator proteins, p53 and p21. Surprisingly, while antigen from H. polygyrus inhibited human colorectal cancer cell migration, it had the opposite effect on mouse colorectal cancer cells, suggesting that its impact on colorectal cancer migration may be, at the very least, species dependent. Using a syngeneic tumour model, the excretory-secretory product from H. polygyrus was shown to significantly increase tumour growth and the expansion of regulatory T cells and neutrophils in the tumour. Similarly, in a model of colitis-associated colorectal cancer this antigen significantly worsened pathology in a TGF-β dependent manner. Undoubtedly, the knowledge gained from this study will contribute to the limited understanding about helminths and the effect that these parasites have on cancer progression.